Recent Studies of Rodent Ultrasonic Vocalizations and Their Use in Experimental Models - Brudzynski, Stefan M.; Burgdorf, Jeffrey (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book includes articles written by over 80 specialists from many countries that demonstrate the biological functions of ultrasonic vocalizations and how they are used in studies of vocal expression of emotional states and in numerous animal models of neuropsychiatric diseases and disorders. Results of investigations of emissions of ultrasonic vocalizations are useful in studies of emotional disturbances, affective disorders, autism spectrum disorders, addiction, developmental abnormalities, and many other pathologies.